Jonathan Strange & Mr. Norrell - Clarke, Susanna (New York and London: Bloomsbury Publishing, 2004)
An alternative history set in 19th-century England around the time of the Napoleonic Wars, it is based on the premise that magic once existed in England and has returned with two men: Gilbert Norrell and Jonathan Strange. Centring on the relationship between these two men, the novel investigates the nature of "Englishness" and the boundaries between reason and unreason, Anglo-Saxon and Anglo-Dane, and Northern and Southern English cultural tropes/stereotypes
Keywords: Novela